Cytochrome C as a benchmark system for a two-layer gold surface with improved surface-enhancement for spectro-electrochemistry. Issue 1 (2010) - Nowak, Christoph; Schach, Denise; Grosserüschkamp, Marc; Knoll, Wolfgang; Naumann, Renate L.C.
Abstract : A two-layer gold surface is developed for use with electrochemistry followed by surface-enhanced infrared absorption spectroscopy (SEIRAS) consisting of a conducting underlayer onto which Au nanoparticles (AuNPs) are grown by self-catalyzed electroless deposition. AuNPs are grown on protruding substructures of the 25 nm thin underlayer. The enhancement factor of the two-layer gold surface is controlled by the growth conditions. Cytochrome c adsorbed to a self-assembled monolayer of mercaptoethanol is used as a benchmark system for the investigation of complex heme proteins from the respiratory chain such as cytochrome c oxidase and the bc1 complex. Under optimum conditions the absorbance of the amide I band of cytochrome c is increased by a factor of 5 vs. classical SEIRAS surface. Reversible reduction/oxidation of cytochrome c on the two-layer gold surface is shown to take place by cyclic voltammetry.